Early Outcomes from Proton Craniospinal Irradiation for Leptomeningeal Metastasis From Solid Tumors - Keng Lam, MD; Lewis F. Nasr, MD; Clark R. Andersen, MS; Kathryn E. Marqueen, MD; Jing Li, MD, PhD; Chenyang Wang, MD; Thomas H. Beckham, MD, PhD; Nazanin K. Majd, MD, PhD; Ashley E. Aaroe, MD; Monica Loghin, MD; Barbara J. O'Brien, MD; Susan L. McGovern, MD, PhD (Advances in Radiation Oncology)
Purpose: Treatment options for leptomeningeal metastasis (LM) are limited. A recent phase 2 study found that proton craniospinal irradiation (pCSI) was well-tolerated and improved survival. We report our experience with pCSI for solid-tumor LM. Methods and Materials: This is a retrospective review of patients treated with pCSI for solid-tumor LM from December 2020 to January 2024 at our center. Patient characteristics were summarized using descriptive statistics. Median overall survival and median central nervous system progression-free survival from the first day of pCSI were estimated using Kaplan-Meier survival curves. Results: We identified 45 patients who completed pCSI. The median age was 54 years (range, 23-79); 73% were female, and 53% lived more than 100 miles from our center. Breast cancer (53%), lung cancer (20%), and melanoma (9%) were the most common primary cancers; 51% of patients had stable systemic disease at LM diagnosis. All had imaging evidence of LM, and 64% of cases were confirmed using cytologic examination of the cerebrospinal fluid. Eighty percent had symptomatic LM, and the median Karnofsky performance scale at LM diagnosis was 80. The median time from primary cancer diagnosis to LM detection was 23.1 months (range, 0-221.3). Fifty-three percent of patients had active brain metastasis at LM diagnosis; 33% of all patients had received prior intracranial radiation. The median time from simulation to pCSI start was 12 days. At the first visit following pCSI, the median Karnofsky performance scale score was 70. During or right after radiation, 76% of patients reported nausea, 51% headache, and 31% fatigue. Following pCSI, 4% received intrathecal chemotherapy, 67% systemic therapy, and 9% hospice care; 18% were observed and 2% lost to follow-up. Median overall survival was 13.7 months (95% confidence interval [CI], 11.2 to not reached), and median progression-free survival was 6.5 months (95% CI, 4.9-12.8). Conclusions: The outcomes in our cohort are comparable to those recently reported in a phase 2 trial. Further study is indicated to determine the optimal candidates for pCSI and sequential therapies.